A relação entre catecismo e catequese - Alves dos Santos , Elismar (Kairós: Revista Acadêmica da Prainha, 2021)
To develop the proposed subject, the article is divided into two parts. The first presents the effort of the Catholic Church in the implementation of some catechisms in the difficult task of evangelization throughout history. Faced with so many controversies related to other religious views on the Catholic doctrine, the catechisms sought to highlight the values espoused by the Catholic Church and the way that the faithful should follow. The second part describes the relationship between Catechism and Catechesis. From the Second Vatican Council, many ecclesial realities have changed. Among them, catechesis. What is the purpose of the Catechism facing the Catechesis? It's antecipated that this needs to be designed as an instrument in the catechetical process. Its purpose lies on the rich transmission of the mystagogic experience to the children of God entrusted to the Church of the Lord.